SELECTION OF FRESH FRUIT BUNCH MARKETING CHANNEL IN SMALLHOLDER OIL PALM PLANTATION IN ACEH PROVINCE - Mawardati, Mawardati (Jurnal Aplikasi Manajemen, 2018)
This research was conducted at smallholder plantation in Aceh Province in January- March 2015. The purpose of this research is to analyze the factors that influence farmers in choosing marketing channel in smallholder oil palm plantation in Aceh Province. The analytical method used in this study was multinomial logit. The result of the analysis shows that several factors, namely the age of farmers, production volume, loan capital, and the price of fresh fruit bunch (FFB) are the factors that become the basis of consideration of farmers in choosing marketing channel of large traders. Based on the result of regression coefficient, it is known that production volume was the most dominant factor affecting the farmers in choosing marketing channel of large traders. Meanwhile, all independent variables which were analyzed did not have a significant effect on the selection of marketing channels of Palm Oil Factory (POF).